2008
DOI: 10.1158/1535-7163.mct-07-2421
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α–induced accentuation in cryoinjury: mechanisms in vitro and in vivo

Abstract: Cryosurgical treatment of solid cancer can be greatly assisted by further translation of our finding that a cytokine adjuvant tumor necrosis factor-A (TNF-A) can achieve complete cancer destruction out to the intraoperatively imaged iceball edge (-0.5°C) over the current clinical recommendation of reaching temperatures lower than -40°C. The present study investigates the cellular and tissue level dose dependency and molecular mechanisms of TNF-A-induced enhancement in cryosurgical cancer destruction. Microvasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…Based on our previously published results, we hypothesized that increased recruitment of neutrophils is essential for the enhanced cryosurgical lesion due to nanoparticle preconditioning 15, 23 . To elucidate the role of the inflammatory cell response, we first investigated the recruitment of neutrophils to DSFC LNCaP tumor tissue during the 4 hour period after NP-TNF administration by myeloperoxidase staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previously published results, we hypothesized that increased recruitment of neutrophils is essential for the enhanced cryosurgical lesion due to nanoparticle preconditioning 15, 23 . To elucidate the role of the inflammatory cell response, we first investigated the recruitment of neutrophils to DSFC LNCaP tumor tissue during the 4 hour period after NP-TNF administration by myeloperoxidase staining.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have shown an increase in the deposition of fibrinogen 4 hours after the injection of NP-TNF suggesting optimal conditions have been created to augment or sustain vascular stasis through thrombosis. Furthermore, NP-TNF alone has been shown previously to increase endothelial cell death alone (another hallmark of a VDA response) 16, 23 . Finally, all of these VDA related mechanisms, which are enhanced by nanoparticle delivery, are occurring within the context of reduced systemic toxicity as indicated by a greater than three-fold increase in maximum tolerated dose in a recent clinical trial 13 .…”
Section: Discussionmentioning
confidence: 95%
“…TNF-α is closely associated with multiple vascular events such as endothelial cell apoptosis, increase in procoagulant activity, decrease in anticoagulant activity, recruitment and adherence of inflammatory cells such as neutrophils, and production of other cytokines [95-97]. In a mouse model of human prostate cancer, it was shown that TNF-α increases the thermal threshold of tissue damage in a dose-dependent manner [37, 97-99]. This augmentation was observed when TNF-α was delivered both locally or systemically, about 3-4 hours before cryosurgery.…”
Section: Adjuvants With Cryosurgerymentioning
confidence: 99%
“…This augmentation was observed when TNF-α was delivered both locally or systemically, about 3-4 hours before cryosurgery. Later, it was also shown that the this enhancement was a result of direct TNF-α action on the endothelium and more importantly on the induction of inflammatory pathways leading to an improved vascular response [99]. But like many other stand–alone cytotoxic drugs used in cancer treatment, the systemic delivery of required amounts of TNF-α is a major obstacle to achieve rapid clinical translation of this finding.…”
Section: Adjuvants With Cryosurgerymentioning
confidence: 99%
“…The dorsal window chamber has found utility in many biomedical research applications, notably in studies of angiogenesis (Dellian et al, 1996; Laschke and Menger, 2007) and tumor progression, evaluation of microvascular-targeted biomolecular therapies (Yuan et al, 1996), evaluation of cryosurgical destruction on human prostate cancer (Chao et al, 2004; Jiang et al, 2008), evaluation of light-based therapies targeting the microvasculature (Choi et al, 2008), and evaluation of topically applied chemical enhancement of light-based therapy (Vargas et al, 2008). Tumor studies have been performed via implantation of tumor cell lines or primary tumor cells into the dorsal window chamber, allowing for direct visualization of the entire tumor and the surrounding vasculature (Dewhirst et al, 2000; Jain et al, 2002).…”
Section: Introductionmentioning
confidence: 99%